Kotak Manihot Food Box Eco-Green Sebagai Kotak Makanan Dari Bahan Dasar Limbah Kulit Singkong - Dona Martilova; Neneng Lisma Sari; Novia Nurrahmawati; Nia Listari; Siska Saputriyani; Natasya Lailatul Syahrani (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Manihot Food Box Eco-Green is an innovative food container made from cassava peel waste. Cassava (Manihot esculenta Crantz) is a plant widely grown in tropical regions, especially in Indonesia. Despite its many uses, cassava peels are often discarded and contribute to environmental pollution. This project aims to process cassava peel waste into eco-friendly food boxes. The production process involves three main stages: survey, production, and marketing. The product is designed with a simple and practical shape, ideal for the food business, and offers significant profit potential. The marketing strategy includes both offline (brochures) and online channels (Shopee, Instagram), with a competitive price of IDR 36,000 per pack (12 units). This project not only presents profitable business opportunities but also helps reduce environmental waste by utilizing cassava peels.